Predictive factors and clinical efficacy of Chinese medicine Shengji ointment in the treatment of diabetic foot ulcers in the elderly: a prospective study - Zhao, Yang; Li, Zheng-Hong; Sheng, Song; Dai, Xin-Yue; Li, Qing-Na; Cao, Wei-Yi; Gao, Rui; Liu, Xing-Fang; Gao, Hong-Yang (Frontiers in Pharmacology, 2023)
Abstract Objective: This study aims to investigate the predictive factors and efficacy of traditional Chinese medicine Shengji Ointment in the treatment of diabetic foot ulcers in the elderly population, with the intent of formulating an effective predictive model for deep diabetic foot ulcer healing. The importance of this research lies in its provision of new perspectives and tools for addressing the severe health impact of diabetic foot ulcers in the elderly population, considering the complexity and diversity of its treatment methods. Methods: The study includes 180 elderly patients with Wagner grade 3-4 diabetic foot ulcers that involve the tendon or fascia. The dependent variable is the initiation time of granulation tissue development. Independent variables encompass demographic information, a treatment strategy including Shengji Ointment, pre-treatment trauma assessment data, routine blood count, and biochemical index test results. Lasso regression is employed for variable selection, and Cox regression is utilized for the construction of a prediction model. A nomogram is generated to authenticate the model. Results: The Chinese Medicine treatment approach, ulcer location, creatinine levels, BMI, and haemoglobin levels are identified as independent predictors of granulation tissue development in diabetic foot ulcers. The combined treatment of Chinese herbal Shengji ointment and bromelain positively influenced granulation tissue development.The location of plantar ulcers, impaired renal functionality, obesity, and anaemia are established as independent risk factors that might influence the speed and probability of ulcer healing. The area under the time-dependent ROC curve fluctuates between 0.7 and 0.8, demonstrating substantial discrimination and calibration of the model. Conclusion: The study ascertains that a combined treatment strategy incorporating Shengji Ointment demonstrates greater effectiveness than the use of cleansing gel debridement alone in facilitating the healing of Wagner grade 3 or higher diabetic foot ulcers. Furthermore, the predictive model developed in this research serves as a valuable tool in evaluating the efficacy of Chinese Medicine treatments like Shengji Ointment for diabetic foot ulcers in the elderly. It aids clinicians in effectively assessing and adjusting treatment strategies, thereby proving its significant application value in clinical practice.